Sintesis Hidroksiapatit Berbahan Tulang Ikan Layar (Istiophorus Platypterus) Menggunakan Metode Presipitasi - Al-Qarny, Uwais; Rauf, Nurlaela (JFT : Jurnal Fisika dan Terapannya, 2024)
Sailfish bone is one of the marine biological wastes that has potential as a source of hydroxyapatite for biomedical applications. This study aims to synthesize hydroxyapatite made from sailfish bone through precipitation method with the effect of variation in calcium precursor mass and phosphate precursor concentration. Sailfish bones were calcined at 900ºC for 3 hours, then reacted with (NH4)2HPO4. The solution was adjusted to pH 8 using NaOH, precipitated for 24 hours at room temperature to produce a homogeneous precipitate, washed with aquades, and filtered. The precipitate was then dried at 100ºC for 2 hours to produce hydroxyapatite. FTIR characterization showed the presence of PO43-, OH-, and CO32- groups in all three samples. Sample C has higher absorption intensity of PO43- and OH- groups than the other two samples. The higher absorption intensity indicates more content of PO43- and OH- groups. XRD analysis showed that the three samples had dominant hydroxyapatite phase. In addition to the hydroxyapatite phase, there is also A-type carbonate apatite phase and B-type carbonate apatite phase. Sample C has the largest average crystal size, which is 28.94 nm.